Strengthening research capacity through the medical education partnership initiative: the Mozambique experience - Noormahomed, Emilia Virginia; Mocumbi, Ana Olga; Preziosi, Michael; Damasceno, Albertino; Bickler, Stephen; Smith, David M; Funzamo, Carlos; Aronoff-Spencer, Eliah; Badaró, Roberto; Mabila, Francisco; Bila, David; Nguenha, Alcido; et al. (Human resources for health, 2013)
Background Since Mozambique’s independence, the major emphasis of its higher educational institutions has been on didactic education. Because of fiscal and human resource constraints, basic and applied research activities have been relatively modest in scope, and priorities have often been set primarily by external collaborators. These factors have compromised the scope and the relevance of locally conducted research and have limited the impact of Mozambique’s universities as major catalysts for national development. Case description We developed a multi-institutional partnership to undertake a comprehensive analysis of the research environment at Mozambique’s major public universities to identify factors that have served as barriers to the development of a robust research enterprise. Based on this analysis, we developed a multifaceted plan to reduce the impact of these barriers and to enhance research capacity within Mozambique. Interventions On the basis of our needs assessment, we have implemented a number of major initiatives within participating institutions to facilitate basic and applied research activities. These have included specialized training programmes, a reorganization of the research administration infrastructure, the development of multiple collaborative research projects that have emphasized local research priorities and a substantial investment in bioinformatics. We have established a research support centre that provides grant development and management services to Mozambique’s public universities and have developed an independent Institutional Review Board for the review of research involving human research subjects. Multiple research projects involving both communicable and non-communicable diseases have been developed and substantial external research support has been obtained to undertake these projects. A sizable investment in biomedical informatics has enhanced both connectivity and access to digital reference material. Active engagement with relevant entities within the Government of Mozambique has aligned institutional development with national priorities. Conclusions Although multiple challenges remain, over the past 3 years significant progress has been made towards establishing conditions within which a broad range of basic, translational and clinical and public health research can be undertaken. Ongoing development of this research enterprise will enhance capacity to address critical locally relevant research questions and will leverage resources to accelerate the development of Mozambique’s national universities.